Industrial Trials of Paste Drying in Spouted Beds Under QDMC - Corrêa, N. A.; Freire, F. B.; Corrêa, R. G.; Freire, J. T. (Drying technology, 2004)
Spouted bed has been extensively investigated by many authors for years, but the issue of controlling its operation still remains in basic developing stages. The present work consists of the application of an advanced control strategy (QDMC-Quadratic Dynamic Matrix Control) to automate the operation of a large-scale spouted bed dryer. The work on control strategies for spouted bed was motivated by the lack of references on this subject and the encouraging results obtained by Corrêa et al. (Corrêa, N.A.; Freire, J.T.; Corrêa, R.G. Improving operability of spouted beds using a simple optimizing control structure. Brazilian Journal of Chemical Engineering 1999 16 (4), 359-368; Corrêa N.A. Corrêa, R.G.; Freire, J.T. Adaptive control of paste drying in spouted bed using the GPC algorithm. Brazilian Journal of Chemical Engineering 2000 17 (4-7), 639-648; Corrêa, N.A.; Corrêa, R.G.; Freire, J.T. Self-tuning control of egg drying in spouted bed using the GPC algorithm. Drying Technology 2002 20 (4), 813-828.) for a laboratory-scale apparatus. The industrial-scale spouted bed dryer has a height of 4 m and a diameter of 66 cm. The same configuration of data acquisition unit, sensors, and interface developed for the laboratory-scale unit was employed. The dryer is capable of processing up to 20 L/h of pasty material. The powder moisture content (Ys), inferred from measurements of temperature at the exhaustion of the bed bulk, and the powder production rate (Pr), measured on-line by an electronic balance, are the controlled variables. The manipulated variables are: the paste inflow rate (W), regulated by an automatic pump, and the electrical power supply for air heating (P), regulated by a thyristor. The bed pressure drop, the airflow rate, and the information from the environment are monitored by means of an interfaced microcomputer. Experimental runs of drying up to 400 kg/day of an Al 2 O 3 10% aqueous suspension were carried out. The results showed that the QDMC control is robust with respect to the main variables involved and is efficient in maintaining the operation of the bed under the constraints of the system. The major aim concerning the scale-up of spouted bed, which is the determination of the minimum amount of energy required to ensure spout stability, was accomplished by the constrained control strategy.